Immunomodulatory effects and anti-Candida activity of lactobacilli in macrophages and in invertebrate model of Galleria mellonella - de Oliveira, Felipe Eduardo [UNESP]; Rossoni, Rodnei Dennis [UNESP]; de Barros, Patricia Pimentel [UNESP]; Begnini, Barbara Evelyn [UNESP]; Junqueira, Juliana Campos [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Leão, Mariella Vieira Pereira; de Oliveira, Luciane Dias [UNESP] (Elsevier, 2017)
Due to the growing number of multi-resistant Candida spp., adjuvant treatments that may help combat these fungal pathogens are relevant and useful. This study evaluated the immunomodulation and anti-Candida activity of Lactobacillus rhamnosus (LR), Lactobacillus acidophilus and Lactobacillus paracasei suspensions, either single- or multiple-strain, in mouse macrophages (RAW 264.7) and Galleria mellonella (GM). Mouse macrophages were activated by different lactobacilli suspensions and challenged with C. albicans (CA). Tumor necrosis factor (TNF)-α, interleukin IL-1β, IL-6 and IL-17 production and cell viability were investigated. LR was the best suspension for stimulating all evaluated cytokines and thus was used in subsequent in vivo assays. Two C. albicans clinical strains, CA21 and CA60, were then added to the GM assays to further confirm the results. LR suspension was injected into the larvae 24 h before challenging with CA. Survival curve, CFU per larva and hemocytes were counted. In the GM, the LR suspension increased the survival rate and hemocyte counts and decreased the CFU per larva counts for all groups. Lactobacilli suspensions presented strain-dependent immunomodulation; however, single suspensions showed better results. Anti-Candida activity was demonstrated by decreased Candida counts in the GM with the use of LR.
Keywords: Lactic acid bacteria; Lactobacillus; Macrophages; Mycology; Probiotic; Yeasts